Microstructure and wear resistance of spherical ceramic particles reinforced FeCoNiCrMn composite coating fabricated by laser directional energy deposition - Zhiyuan Liu; Yongcun Li; Yong Wang (Journal of Materials Research and Technology)
FeCoNiCrMn coatings have good plasticity and toughness, but it is difficult to meet the increasing wear resistance requirements. To improve the tribological properties of FeCoNiCrMn coating, WC particles were added to the coating. The effect of WC particles (0 wt% and 15 wt%) on the microstructure and wear resistance was studied. The impact of WC particles against FeCoNiCrMn was evaluated by XRD analysis, microstructure morphology, Vickers hardness analysis, and wear test. The results show that the FeCoNiCrMn exists as an FCC single phase, and adding WC particles produces a new precipitated phase (Cr23C6). The hardness of WC/FeCoNiCrMn composite coating (265.94HV) is 1.5 times higher than that of FeCoNiCrMn coating (173.41HV). In addition, the addition of WC particles promoted the oxidation wear of the composite coating, the wear rates of WC/FeCoNiCrMn under 10 N and 15 N loads are 2.8 × 10−5 mm3/(N·m) and 1.75 × 10−5 mm3/(N·m). The wear mechanism of WC/FeCoNiCrMn composite coating is mainly oxidation wear and abrasive wear, and with the increase of load, the degree of oxidation wear and abrasive wear of WC/FeCoNiCrMn composite coating increased. WC/FeCoNiCrMn composite coating shows better wear resistance than FeCoNiCrMn coating.